Bulk- and Powder Surface Exchange Coefficients of (La, Sr)CoO3-d. (11th January 2017) - Chiba, HIroshi; Yashiro, Keiji; Hashimoto, Shin-ichi; Kawada, Tatsuya
Abstract : LSC64 have been recognized as a promising cathode for SOFC. Their high oxide ion conductivity makes oxygen reduction reaction possible to occur not only at triple-phase boundary but also on two-phase boundary of an electrode and gas phase. Thus, it is important to study the surface exchange kinetics to understand the surface oxygen reduction process. In this study, we attempted to determine the surface exchange kinetics by pulse isotope exchange. This is innovative approach to determine k by observe the sample response when 16 O exchanged by the isotope. The response and k will be discussed in this study.